Rottlerin increases cardiac contractile performance and coronary perfusion through BK(Ca++) channel activation following cold cardioplegic arrest in isolated hearts - Clements, Richard T (2011)
BACKGROUND: Cardioplegia and cardiopulmonary bypass(CP/CPB) subjects myocardium to complex injurious stimuli that can result in cardiomyocyte and vascular contractile abnormalities. Rottlerin, originally identified as a PKCδ inhibitor has a number of known additional effects that may be beneficial in the setting of CP/CPB. We tested the hypothesis that rottlerin would mitigate deleterious effects associated with CP/CPB. METHODS AND RESULTS: Langendorff-perfused isolated rat hearts were subjected to 2 hours intermittent cold (10 deg C) cardioplegia (St Thomas II) followed by 30 min normothermic reperfusion. Cardioplegia was delivered every 30 min, for 1 min. Hearts were treated with (CP+R, n=7) or without (CP, n=9) the PKCδ inhibitor, rottlerin (1μM) and/or the BK(Ca++) channel inhibitor Paxilline (100 nM) supplied in the cardioplegia. Hearts constantly perfused with Krebs-Heinslet buffer served as controls (n=6). Baseline parameters of cardiac function were similar between groups. CP resulted in reduced cardiac function (LVDP:39±3.8%,±dP/dt: 32±4.4%,-41±5.1% decrease compared to baseline). Treatment with 1uM Rottlerin significantly improved CP-induced cardiac function (LVDP: 20±5.9%, ±dP/dt: 5.2 ±4.5%, -11.6 ± 4.7% decrease versus baseline, (p < .05 CP+R vs CP)). Rottlerin also caused a significant increase in coronary flow post reperfusion (CP 34±4.2% decrease from baseline, vs CP+R 26±9.6% increase over baseline, p=.01). Independent of vascular effects, CP significantly decreased isolated myocyte contraction which was restored by rottlerin treatment. The BK(Ca++) channel inhibitor greatly reduced the majority of beneficial effects associated with Rottlerin. CONCLUSIONS: Rottlerin significantly improves cardiac performance following cardioplegic arrest via improved cardiomyocyte contraction and coronary perfusion.